Determining Factors Affecting Islamic Social Reporting in Registered Companies at Jakarta Islamic Index 70 - Hidayati, Amalia Nuril; Rohmah, Laelatur (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2023)
Islamic Social Reporting (ISR) refers to the disclosure of social responsibility based on Islamic law. This reporting is essential for Muslim investors engaged in the Indonesia Stock Exchange. The aim of this investigation was to assess the impact of profitability, leverage, company size, liquidity, and company age on Islamic Social Reporting. Employing a quantitative approach with an associative research type, this study utilized purposive sampling. Analysis techniques included classical assumption tests, multiple linear regression tests, T tests, F tests, and determination coefficient tests. The findings indicated that, individually, profitability, company size, and liquidity positively and significantly influenced Islamic Social Reporting, while other variables did not exhibit a significant impact. Conversely, collectively, all variables demonstrated a positive and significant effect on Islamic Social Reporting. The implications of this research highlight the importance of utilizing the findings as guidance for companies listed in the Jakarta Islamic Index 70 to promptly integrate and disclose Islamic Social Reporting in their annual reports.